Perfect square trinomial:
(a – b)2 = (a – b)(a – b) = a2 – 2ab + b2
Find the product of (k – 9)2 using the perfect square trinomial rule shown on the left.



The product (k – 9)2 can also be written as .

The product is k2 – k + .

Respuesta :

Answer:

k² - 18k + 81

Step-by-step explanation:

Using the given model then

(k - 9)² with a = k and b = 9

= k² - 2(k)(9) + 9²

= k² - 18k + 81

Answer:

Perfect square trinomial:

(a – b)2 = (a – b)(a – b) = a2 – 2ab + b2

Find the product of (k – 9)2 using the perfect square trinomial rule shown on the left.

The product (k – 9)2 can also be written as

✔ (k – 9)(k – 9)

.

The product is k2 –

✔ 18

k +

✔ 81

.

Step-by-step explanation: